Influence of the Casing Eccentricity on the Cement Sheath Sealing Integrity in the Tie-Back Interval Under the Complex Temperature and Pressure Conditions of Deep-Water Oil and Gas Wells - Li, Zhong; Wu, Yi; Xie, Renjun; Wu, Zhiqiang (Frontiers in Energy Research, 2022)
The integrity of cement sheath seals in casing connection sections is an important part of preventing air channelization. It is of great significance to evaluate the failure mechanism of cement sheath seals in casing connection sections under complex temperatures, pressures, and casing eccentricities. Based on the self-developed high-temperature and high-pressure full-size casing connection period of the cement sheath seal integrity evaluation device and the casing loading/unloading casing eccentricity influence on the cement sheath seal failure under the experimental conditions, it is concluded that the casing pressure changes, annulus preset pressure, and casing eccentricity influence the law of cement sheath seal integrity. The results show that the following: ① Casing eccentricity has an important influence on the failure of the cement sheath seal when the casing is loaded, and to ensure the integrity of the cement sheath seal the casing should be greater than 75%; ② in the case that the annular pressure is not set, casing eccentricity has little influence on the integrity of the cement annular seal during casing unloading, and sealing failure occurs when pressure unloading is 15-20 MPa; ③ when there is a preset pressure in the annulus, casing eccentricity has a great influence on seal failure during unloading. The greater the preset pressure in the annulus is, the better the seal integrity of the cement annulus. The research results provide an important basis for ensuring the integrity of cement sheath seals in casing connection sections.